Comparison of dynamic contrast‐enhanced MR, ultrasound and optical imaging modalities to evaluate the antiangiogenic effect of PF‐03084014 and sunitinib. (27th February 2014) - Zhang, Cathy C.; Yan, Zhengming; Giddabasappa, Anand; Lappin, Patrick B.; Painter, Cory L.; Zhang, Qin; Li, Gang; Goodman, James; Simmons, Brett; Pascual, Bernadette; Lee, Joseph; Levkoff, Ted; et al.
Abstract Noninvasive imaging has been widely applied for monitoring antiangiogenesis therapy in cancer drug discovery. In this report, we used different imaging modalities including high‐frequency ultrasound (HFUS), dynamic contrast enhanced‐MR (DCE‐MR), and fluorescence molecular tomography (FMT) imaging systems to monitor the changes in the tumor vascular properties after treatment with γ‐secretase inhibitor PF‐03084014. Sunitinib was tested in parallel for comparison. In the MDA‐MB‐231Luc model, we demonstrated that antiangiogenesis was one of the contributing mechanisms for the therapeutic effect of PF‐03084014. By immunohistochemistry and FITC‐lectin perfusion assays, we showed that the vascular defects upon treatment with PF‐03084014 were associated with Notch pathway modulation, evidenced by a decrease in the HES1 protein and by the changes in VEGFR2 and HIF1α levels, which indicates down‐stream effects. Using a 3D power Doppler scanning method, ultrasound imaging showed that the% vascularity in the MDA‐MB‐231Luc tumor decreased significantly at 4 and 7 days after the treatment with PF‐03084014. A decrease in the tumor vessel function was also observed through contrast‐enhanced ultrasound imaging with microbubble injection. These findings were consistent with the PF‐03084014‐induced functional vessel changes measured by suppressing the Ktrans values using DCE‐MRI. In contrast, the FMT imaging with the AngioSence 680EX failed to detect any treatment‐associated tumor vascular changes. Sunitinib demonstrated an outcome similar to PF‐03084014 in the tested imaging modalities. In summary, ultrasound and DCE‐MR imaging successfully provided longitudinal measurement of the phenotypic and functional changes in tumor vasculature after treatment with PF‐03084014 and sunitinib.